2022
DOI: 10.1128/mbio.03456-21
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulatory Role of Chromatin Remodeler ISW1 in Coordinating Cellulase and Secondary Metabolite Biosynthesis in Trichoderma reesei

Abstract: Microorganisms, including Trichoderma reesei , constantly face the challenge to outcompete other species to ensure efficient colonization in their natural habitat. They achieve this usually by adopting two alternative strategies by either maintaining fast growth on limited nutrient resources or producing a versatile array of secondary metabolites to fight against competitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…It is thus highly unlikely that the enhanced sorbicillinoid biosynthesis results from the impaired vegetative growth. Similarly, increased SOR gene expression has been also found in our recent studies with a chromatin remodeller whose absence compromised growth (Cao et al, 2022). Nevertheless, the impaired vegetative growth could be a mimicry of antagonism when confronted with other fungi that may evoke a self-protection mechanism to promote sorbicillinoid biosynthesis in the absence of TrDim5.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is thus highly unlikely that the enhanced sorbicillinoid biosynthesis results from the impaired vegetative growth. Similarly, increased SOR gene expression has been also found in our recent studies with a chromatin remodeller whose absence compromised growth (Cao et al, 2022). Nevertheless, the impaired vegetative growth could be a mimicry of antagonism when confronted with other fungi that may evoke a self-protection mechanism to promote sorbicillinoid biosynthesis in the absence of TrDim5.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that T. reesei orthologues of velvet protein complex modulated sorbicillinoid synthesis (Aghcheh et al, 2014 ; Karimi‐Aghcheh et al, 2013a ; Seiboth et al, 2012 ). Recently, our studies suggested that chromatin remodelling factor Isw1 participated in the regulation of sorbicillinoid synthesis in T. reesei (Cao et al, 2022 ). Otherwise, little evidence has been found for T. reesei SOR gene cluster regulation, especially at the chromatin level, to guide sorbicillinoid biosynthesis.…”
Section: Introductionmentioning
confidence: 98%
“…An involvement of MAPkinases of T. reesei in regulation of secondary metabolism has not been tested previously. Sorbicillin production is connected to the regulation of cellulase gene expression and carbon catabolite repression in T. reesei 50,87,88 . Therefore, we assessed this function with a photometric screening for yellow pigments representing mainly sorbicillin derivatives, which show a typical light absorbance maximum close to 370 nm.…”
Section: Mapkinases Regulate Cellulase Transcription and Secreted Act...mentioning
confidence: 99%
“…Among them, the mangrove-derived fungal genus Trichoderma produces a diverse array of secondary metabolites including alkaloids, polyketides, terpenoids, phenols, lactones, and various hybrids of the aforementioned classes [2][3][4][5][6]. Sorbicillinoids, a marker secondary metabolite of Trichoderma reesei (T. reesei), have a characteristic sorbyl side chain and a cyclic hexaketide nucleus in the structures [7,8]. Since sorbicillin was first discovered from Penicillium notatum in 1948, more than 100 analogs of sorbicillinoids have been reported and they can be classified into monomeric-, bi-, tri-, and hybrid sorbicillinoids by the number of sorbicillinoid construction units [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Sorbicillinoids, a marker secondary metabolite of Trichoderma reesei ( T . reesei ), have a characteristic sorbyl side chain and a cyclic hexaketide nucleus in the structures [ 7 , 8 ]. Since sorbicillin was first discovered from Penicillium notatum in 1948, more than 100 analogs of sorbicillinoids have been reported and they can be classified into monomeric-, bi-, tri-, and hybrid sorbicillinoids by the number of sorbicillinoid construction units [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%